Do South Korean adults have insufficient levels of physical activity? Domain patterns and associations with self-rated health - Kyoung Ae Kong (PLoS ONE, 2026)
Objectives The study aimed to evaluate domain-specific physical activity (PA) patterns in South Korea, where the prevalence of insufficient PA is high, and assess their association with self-rated health (SRH). Methods Data from 32,005 South Korean adults aged 20–79 from the Korean National Health and Nutrition Examination Survey (2016–2021) were analyzed. Domain-specific PA (leisure-time (LTPA), transportation-related (TPA), and work-related (OPA)) were measured using the Global Physical Activity Questionnaire. PA was categorized into <10, 10–149, and ≥150 min/week, labeled as “inactive,” “insufficient,” and “meeting PA guidelines (PAG).” Each individual’s primary PA domain was defined by the domain with the largest proportion of their total PA time. Logistic regression was used to examine associations between PA patterns and good SRH. Results In total, 46.3% met PAG, while 30.8% were inactive. TPA was the primary domain for 59.0% of non-inactive individuals. This emphasis on TPA was pronounced among women, the elderly, and those with insufficient PA. Only 8.7% had ≥ 10 minutes of continuous OPA per week, and 19% met PAG through LTPA alone. LTPA showed a clear positive dose-response relationship with good SRH. TPA showed a weak positive association, while OPA showed an inverse association. Conclusions The high prevalence of insufficient PA among Korean adults is likely primarily attributed to low levels of OPA. TPA is the primary PA domain. Only LTPA showed clear health benefits regarding SRH, but a large proportion did not meet PAG through LTPA. Monitoring domain-specific PA patterns is needed for developing effective PA promotion strategies in Korea.